The Bhagavad Gita - 20160731 frey50; Eknath, Easwaran, 1910-1999. (Tomales, CA : Nilgiri Press, 2007)
In the Bhagavad Gita, Prince Arjuna asks direct, uncompromising questions of his spiritual guide on the eve of a great battle. In this expanded edition of the most famous -- and popular -- of Indian scriptures, Eknath Easwaran contextualizes the book culturally and historically and explains the key concepts of Hindu religious thought and the technical vocabulary of yoga. Chapter introductions, notes, and a glossary help readers understand the book's message. Most importantly, this translation uses simple, clear language to impart the poetry, universality, and timelessness of the Gita's teachings.--From publisher description.
Previously published: c1985.
Includes index.
Keywords: Hinduism; Sacred books